DEVELOPMENT OF PRESCHOOL EDUCATION (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the development of preschool education as a fundamental stage in human learning and personality formation. It discusses the evolution of preschool systems, pedagogical approaches, and educational standards from historical and modern perspectives. The study also highlights the significance of early childhood education in shaping cognitive, social, and emotional skills, emphasizing the role of teachers, families, and government policy in creating an effective preschool framework. Finally, it explores global trends and innovative methods that contribute to improving the quality and accessibility of preschool education in the 21st century.